The Cellular Prion Protein: A Player in Immunological Quiescence - Bakkebø, Maren K.; Mouillet-Richard, Sophie; Espenes, Arild; Goldmann, Wilfred; Tatzelt, Jörg; Tranulis, Michael A. (Frontiers in Immunology, 2015)
Despite intensive studies since the 1990s, the physiological role of the cellular prion protein (PrPC) remains elusive. Here, we present a novel concept suggesting that PrPC contributes to immunological quiescence in addition to cell protection. PrPC is highly expressed in diverse organs that by multiple means are particularly protected from inflammation, such as the brain, eye, placenta, pregnant uterus and testes, while at the same time it is expressed in most cells of the lymphoreticular system. In this paradigm, PrPC serves two principal roles: to modulate the inflammatory potential of immune cells and to protect vulnerable parenchymal cells against noxious insults generated through inflammation. Here we review studies of PrPC physiology in view of this concept.